PENGARUH PERSEPSI RISIKO, PERSEPSI KEMUDAHAAN, DAN PERSEPSI MANFAAT TERHADAP MINAT BELANJA DI BUKALAPAK - amelia sarah nurohmah; Guston Sitorus; Arifin Siagian (Jurnal Satya Mandiri Manajemen dan Bisnis, 2024)
This research aims to determine the influence of Perception of Risk, Perception of Convenience, and Perception of Benefits on Shopping Interest at Bukalapak. This research design uses casual quantitative. The population in this study were all Bukalapak application users in DKI Jakarta, while the sample used was 100 respondents. The data analysis method uses Multiple Linear Regression and SPSS 27 software. The results of this research are that Perception of Risk, Perception of Ease, and Perception of Benefit have a positive and significant effect on shopping interest at Bukalapak, this can be proven from the Fcount value of 37.907 > Ftable 2.70 and the sig value (0.000) < α (0.05) and The coefficient of determination value is 54.2%. Risk perception has a positive and significant effect on shopping interest at Bukalapak, this can be proven from the tcount value of 3.612 > ttable 0.1985 and has a significance value of 0.000 which is smaller than 0.05. Perception of ease has a positive and significant effect on shopping interest at Bukalapak, this can be proven from the tcount value of 4.001 > ttable 0.1985 and has a significance value of 0.000 which is smaller than 0.05. Perception of Benefits has a positive and significant effect on shopping interest at Bukalapak, this can be proven from the tcount value of 4.378 > ttable 0.1985 and has a significance value of 0.000 which is smaller than 0.05.